2022
DOI: 10.1111/plb.13416
|View full text |Cite
|
Sign up to set email alerts
|

Drought affects the performance of native oak seedlings more strongly than competition with invasive crested wattle seedlings

Abstract: Two of the most important processes threatening vulnerable plant species are competitive displacement by invasive alien species and water stress due to global warming. Quercus lusitanica, an oak shrub species with remarkable conservation interest, could be threatened by the expansion of the invasive alien tree Paraserianthes lophantha. However, it is unclear how competition would interact with predicted reductions in water availability due to global climate change. We set up a full factorial experiment to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…In another study by Santamarina et al . (2022) it has been shown that invasive species can threaten seedling establishment, particularly if drought stress intensifies. The competitive effect of an invasive shrub species ( Paraserianthes lophantha (Willd.)…”
Section: Species Mixture Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by Santamarina et al . (2022) it has been shown that invasive species can threaten seedling establishment, particularly if drought stress intensifies. The competitive effect of an invasive shrub species ( Paraserianthes lophantha (Willd.)…”
Section: Species Mixture Effectsmentioning
confidence: 99%
“…In this special issue, a broad range of observational and experimental studies are provided that relate to tree health, drought and heat stress resistance and recovery at multiple levels, including causes and consequences of drought-induced tree mortality. The studies use a wealth of approaches, covering remote sensing West et al 2022), ground-based monitoring (Frei et al 2022;George et al 2022), different management regimes (Bose et al 2021;Meyer et al 2022), including species mixture effects Santamarina et al 2022), field studies on wood formation plasticity (Larysch et al 2022), acclimation potential at the leaf level (Weithmann et al 2021;Petrik et al 2022) and recovery potential at the tree level (Kn€ uver et al 2022). These are supported by field- (Guan et al 2022;Kahmen et al 2022;Kn€ uver et al 2022) and lab-based (Kunert et al 2021;Petruzzellis et al 2021;McAdam et al 2022) ecophysiological studies that will increase our understanding of the impacts and consequences of global change-type droughts.…”
mentioning
confidence: 99%
“…For example, differences in drought vulnerability among co-existing species were strongly related to structural-morphological traits, in particular root water uptake depth (Kahmen et al 2022). Interactions between species can further enhance (or buffer) drought impacts, depending on the severity of the drought Santamarina et al 2022).…”
mentioning
confidence: 99%
“…2022) and species interaction effects in mixtures (Haberstroh & Werner 2022; Santamarina et al . 2022), to results from remote sensing (Haberstroh et al . 2022; West et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation